Improving students’ geometric mathematical problems through the GeoGebra-Assisted "5E" Learning Cycle - Pingpor, Piyathida; Yonwilad, Wannatida (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2023)
This study aims to investigate the effectiveness of the GeoGebra-assisted 5E learning cycle toward students’ understanding of mathematical concepts. This study was a quasi-experiment with a pre-test and post-test control group design. The cluster random sampling technique was used to select samples from each group, which included 25 seventh-grade students. The data collected in this study were students’ mathematical prior knowledge obtained by giving objective tests before starting the learning process and students' mathematical conceptual understanding obtained by giving an essay test at the end of the learning process. The hypotheses were tested using a t-test. The findings revealed that the GeoGebra-assisted 5E learning cycle has an advantageous effect on students' comprehension of mathematical concepts, where t = 16.50* and p = 0.0001. The findings of this research implied that the GeoGebra-assisted 5E learning cycle model can be used as an alternative learning model to improve students' understanding of mathematical concepts.